Pelatihan mengajar dalam bahasa Inggris dengan metode role play untuk Guru SMA Pangudi Luhur Don Bosko - Krismalita Sekar Diasti; Caecilia Titiek Murniati; Heny Hartono (Universitas Sanata Dharma, 2026)
This community service aimed to provide English language training for teachers at Pangudi Luhur Don Bosko Senior High School, Semarang, Indonesia. This training focuses on improving teachers’ English proficiency for teaching in the classroom. The community service involved 12 non-English subject teachers. The training began in November 2024 and ended in January 2025. The material given to the teachers focused on classroom expression. To facilitate teachers' speaking practices, role-play activities were chosen as they could simulate real classroom situations. At the end of the training, teachers were asked to perform micro-teaching using classroom expressions discussed in previous meetings. Through this English language training, teachers of Pangudi Luhur Don Bosko Senior High School could improve their pedagogical competence, especially in teaching non-English subjects using English.